ANALISIS SYNGAS GASIFIKASI BATUBARA TIPE DOWNDRAFT DITINJAU DARI VARIASI UKURAN BATUBARA DAN TINGGI ISIAN PACKING ABSORBER - Fadjrin Ismaily, Muhammad; Kurniawaty, Fegi; Syarif, Aida; Rusnadi, Irawan; Febriana, Ida (Politeknik Negeri Sriwijaya, 2021)
Coal gasification is the process of converting low rank coal into syngas which can be used as fuel. One of the factors that affect the quality of syngas is the size of coal particles. Meanwhile, to produce clean syngas, the gas from the combustion reactor is flowed through a packed bed absorber filled with marbles to reduce the incompatible particulate gases that are still contained in the syngas. The variations in the size of the coal used in this study are 3-4 cm, 5-6 cm, and 7-8 cm. While the variation of the height of the packing absorber filling used was 9.75 cm, 19.5 cm, 29.25 cm and 39 cm. The composition of the best combustible gas from the variation of coal size and the variation in the filling height of the absorber packing is found in the coal size 3-4 cm, and the packing filling height is 39 cm. With combustible gases (CO, H2 and CH4) produced by 10.9%, 10.5% and 0.9%, the volume of O2 and CO2 is 0.1% and 10.1%, the syngas volume of the absorber output is 2473.47 m3 and the LHV syngas is 6.932 MJ/kg.